2005
DOI: 10.1200/jco.2005.02.0057
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Stem-Cell Transplantation Using a Reduced-Intensity Conditioning Regimen Has the Capacity to Produce Durable Remissions and Long-Term Disease-Free Survival in Patients With High-Risk Acute Myeloid Leukemia and Myelodysplasia

Abstract: The extended follow-up in this series identifies a high risk of early disease relapse but provides evidence that RIC allografts can produce sustained DFS in a significant number of patients with AML who would be ineligible for allogeneic transplantation with myeloablative conditioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
141
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(154 citation statements)
references
References 29 publications
11
141
1
1
Order By: Relevance
“…20 ATG did not impact the 2-year CI of relapse in our study, which differs from the CIBMTR one in regard to patients' age (only 55 years and older), stem cell source (only PBSC), disease type and status (only AML in CR1), and donor compatibility (only matched donor). However, our results are in accordance with earlier report by other smaller studies, [21][22][23] as well as to a recent publication by our group on 1250 adult patients with de novo AML in CR1 given PBSC from HLA-identical siblings after chemotherapy-based RIC regimen, where the use of ATG and the use of alemtuzumab were each associated with a lower risk of chronic GVHD, but a similar risk of relapse. 24 Because of the selection criteria (only patients 8/8 matched were considered), we were unable to assess the impact of mismatches on the risk of chronic GvHD and eventually NRM.…”
Section: Discussionsupporting
confidence: 93%
“…20 ATG did not impact the 2-year CI of relapse in our study, which differs from the CIBMTR one in regard to patients' age (only 55 years and older), stem cell source (only PBSC), disease type and status (only AML in CR1), and donor compatibility (only matched donor). However, our results are in accordance with earlier report by other smaller studies, [21][22][23] as well as to a recent publication by our group on 1250 adult patients with de novo AML in CR1 given PBSC from HLA-identical siblings after chemotherapy-based RIC regimen, where the use of ATG and the use of alemtuzumab were each associated with a lower risk of chronic GVHD, but a similar risk of relapse. 24 Because of the selection criteria (only patients 8/8 matched were considered), we were unable to assess the impact of mismatches on the risk of chronic GvHD and eventually NRM.…”
Section: Discussionsupporting
confidence: 93%
“…Unrelated umbilical cord blood (UCB) HSCT had similarly successful outcomes as volunteer unrelated donors (URD) transplants using RI conditioning [18]. These data add to an increasing body of evidence [19][20][21][22] that RI HSCT can be clinically potent with an antileukemia effect capable of inducing and maintaining a long term remission in these aggressive myeloid malignancies. The preferred intensity within the spectrum of RI or non-MA conditioning regimens for myeloid leukemia continues to be a subject of study [16,23].…”
Section: Discussionmentioning
confidence: 83%
“…RI regimens have been reported to reduce the cytokine release and damage to mucosal tissues and result in less aGVHD compared with MA, which can contribute to a lower TRM. The TRM using RI regimens has been reported from 5% [25] to nearly 20% [20,22,26]. TRM varies with the patient population, the time point at which it is assessed following HSCT, and the intensity of the RI regimen.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Allo-SCT following reduced-intensity conditioning (RIC) is being increasingly used as treatment for patients with AML who are too old or too frail to tolerate high-dose conditioning regimens. [7][8][9][10][11][12][13][14][15][16][17][18][19] The goal of RIC allo-SCT is to harness the GVL effect, 7 while minimizing toxicities and the risk of GVHD. However, this is a delicate balance as a number of prior studies have shown a lower risk of relapse in AML patients who experienced chronic GVHD after RIC allo-SCT compared with those patients who did not, [10][11][12]20,21 while some other studies failed to find such an association.…”
Section: Introductionmentioning
confidence: 99%